A Study on the Need for Green Activity Program in Fostering Green Consumer Behavior in Primary Schools - Rahmawati, Deasy; Supriatna, Nana; Sapriya, Sapriya; Yuliawati, Astri (Laboratory of Islamic Religious Education Faculty of Tarbiyah and Teacher, 2025)
The development of environmental values and pro-environmental behavior must begin from an early age, particularly within primary education. Schools, therefore, have a strategic role in shaping sustainable habits through educational interventions. This study aims to assess the need for educational programs that integrate green activities and to evaluate teachers’ and principals’ understanding of green consumer behavior. Using an Ex Post Facto research design and purposive sampling, data were collected from 32 fifth-grade teachers and 32 public primary school principals in Bandung, Indonesia. A validated Guttman-scale questionnaire was used, and data were analyzed using descriptive qualitative methods. The results showed that all respondents recognized the importance of implementing green activities and instilling green consumer behavior. The gap between conceptual understanding and classroom practice—particularly among teachers—indicates a need for more targeted capacity-building. This study highlights the importance of developing integrated, project-based, and contextually relevant learning models to promote environmental literacy and responsible consumption, contributing to the broader goals of environmental education and character development.